2012
DOI: 10.1186/1477-7525-10-148
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about chelation among thalassemia patients

Abstract: BackgroundUnderstanding patients’ views about medication is crucial to maximize adherence. Thalassemia is a congenital blood disorder requiring chronic blood transfusions and daily iron chelation therapy.MethodsThe Beliefs in Medicine Questionnaire (BMQ) was used to assess beliefs in chelation in thalassemia patients from North America and London in the Thalassemia Longitudinal Cohort (TLC) of the Thalassemia Clinical Research Network (TCRN). Chelation adherence was based on patient report of doses administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…A previous study conducted by Trachtenberg et al [5] on patients with thalassemia revealed similar findings. In comparison with other chronic disorder, necessity of iron chelation was higher than that in patients with rheumatoid arthritis and concerns about chelation were lower than those patients with rheumatoid arthritis [6].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A previous study conducted by Trachtenberg et al [5] on patients with thalassemia revealed similar findings. In comparison with other chronic disorder, necessity of iron chelation was higher than that in patients with rheumatoid arthritis and concerns about chelation were lower than those patients with rheumatoid arthritis [6].…”
Section: Discussionsupporting
confidence: 72%
“…This high adherence to chelation therapy indicates that patients understand the importance of chelation therapy and the complications associated with not using the therapy. Previous study conducted on thalassemic patients found similar result [5]. However, this rating was based on self-administered questionnaire and therefore, it depended on participants' recall and they might overestimate their responses toward adherence.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…3 Therefore, an iron chelation therapy is required to prevent complications in other organs. 4 Currently, in Indonesia, there are three kinds of iron chelation drugs available, which are deferoxamine (DFO) given subcutaneously, deferiprone (DFP) and defarasirox (DFX) given orally. 2 DFP and DFX are more often used in hospitals because there are less expensive and the level of compliance is higher than DFO.…”
Section: Introductionmentioning
confidence: 99%